Optimal assessment share structured of Pharmacoeconomics for medical drugs according to minimax criterion. - Yagudina, Roza; Borodin, Alex; Kulikov, Andrey; Protsenko, Marina; Serpik, Vyacheslav; Vigodchikova, Irina; Dubinina, Anastasia (Pharmacy Practice (1886-3655))
Objective: To develop a comprehensive methodology for the optimal assessment of the share of the use of medicines, based on the procedure for ranking drugs according to the pharmacoeconomic point scale and the minimax criterion was applied. Methods: The author's approach is based on the minimax principle and allows solving the problem of optimizing the pharma drug portfolio based on available data, without the need to obtain the parameters of the Markowitz model associated with correlation analysis of data. Results: The authors obtained the optimal distribution of medicines in group A, B: 37% to 63%, which the authors consider a promising recommendation for a pharmaceutical company. The use of a similar approach, which does not contradict the Markowitz methodology, but allows us to reasonably accept the parameters of the model and give the optimal solution for the share distribution of drugs in medical practice. Conclusion: These mathematical tools, justified and equipped with an alternative confirmation, the minimax task can and should take a significant place in the complex pharma-analytical methodology of the management of large companies supplying concomitant drugs to the Russian and foreign market.